Cultures of gendered violence: An integrative review of measures of attitudinal support for violence against women - Powell, Anastasia (The Australian and New Zealand journal of criminology, 2018)
National and international research has repeatedly identified the specific gendered nature and context of women’s victimisation of violence, whereby women are disproportionately victims of sexual and partner violence and overwhelmingly at the hands of known male perpetrators. As such, violence against women warrants a targeted and substantial focus, within overall violence reduction and prevention efforts. In the Australian policy context, there is an emerging and influential focus on attitudes towards violence against women as key targets for primary prevention and as foci for monitoring progress in reducing this violence. The Australian National Community Attitudes Towards Violence Against Women Survey was established to estimate community-level understanding of and attitudes towards violence against women. It has arguably evolved into an important instrument both for monitoring shifts in Australians’ knowledge and attitudes, as well as for directing primary prevention efforts. The purpose of this article is to provide an integrative review in relation to one of the key dimensions of the national community attitudes survey: violence supportive attitudes (see Webster et al., 2014). Here, we seek to identify patterns in defining and measuring attitudes that support violence against women, as well as advance the field by offering recommendations for progressing the measurement of violence supportive attitudes in Australia in the future.